Pemberdayaan Perempuan dalam Meningkatkan Ekonomi Keluarga Melalui Kelompok Aurifanta di Desa Salur Latun Kabupaten Simeulue - Mandala, Aria Fiki (Journal of Management and Economics Innovation, 2025)
This study discusses the role of the Aurifanta Women's Group in enhancing the economic well-being of families in Salur Latun Village, Simeulue District. The primary objective of this research is to analyze how the Aurifanta Group contributes to increasing household income for women, expanding access to economic resources, and fostering changes in economic decision-making at the family level. This research employed a qualitative method using a case study approach through in-depth interviews, participatory observations, and documentation of group activities. The findings reveal that after joining the group, members were able to earn additional monthly incomes ranging from IDR 250,000 to IDR 600,000 from the sale of woven pandanus mats. Moreover, they gained access to capital in the form of financial assistance and business mentoring provided by the village government, along with facilitated access to raw materials sourced from local natural resources. Women’s involvement significantly increased in all aspects of the production and marketing processes. However, the group still faces challenges such as the lack of advanced technical training and limited market access, particularly outside the region and on digital platforms. The conclusion of this research is that the Aurifanta Group has had a significant positive impact on women’s economic empowerment and household resilience. It is recommended that future programs focus on advanced training such as digital marketing, creative product packaging, basic financial recordkeeping for small businesses, and innovation in woven product design to ensure the group’s business growth and sustainability.